SCIENTIFIC FUNDAMENTALS OF INTEGRATION AS ONE OF THE TRENDS DEVELOPMENT OF THE MODERN SCHOOL - Shpachuk, L.R. (Pedagogy of Higher and Secondary Education, 2022)
The article has made an attempt to define the scientific grounds of integration, to give a broad online its potential in terms o f the teaching process in modern school